Kesediaan Membayar (Willingness To Pay) Petani Padi pada Layanan Irigasi di Desa Mojomanis, Kecamatan Kwadungan, Kabupaten Ngawi - Oktaviani, Alvina Widya; Laily, Dona Wahyuning; Fitriana, Nisa Hafi Idhoh (Universitas Galuh, 2025)
Irrigation is an important factor in supporting and increasing agricultural production. For the smooth running of irrigation in Mojomanis Village, awareness is needed from farmers for irrigation fees/pump rent. The purpose of this research is to analyze the characteristics of farmers in Mojomanis Village, analyze the value of farmers' willingness to pay, and analyze what affects the ability of farmers to pay for irrigation services. The analysis approach of this research includes descriptive analysis, contingent valuation method, and multiple linear regression analysis. The results showed that farmers are generally older with male farmers dominating, the majority of farmers' education level is only elementary school level, farming experience is generally 31-40 years, the land area owned by farmers is generally 0.17 hectares, the average cultivated land is owned by farmers and farmers' income is classified as moderate. The average value of willingness to pay (EWTP) of all respondents who are willing to pay for irrigation services/pump rent is in the high category and the total value of willingness to pay (TWTP) for all respondent farmers is also quite high. Factors that significantly affect the willingness to pay (WTP) of farmers are the variable number of family dependents, land area, and income of farmers.